Off‐Fault Deformation in Regions of Complex Fault Geometries: The 2013, Mw7.7, Baluchistan Rupture (Pakistan). Issue 11 (10th November 2022) - Antoine, S. L.; Klinger, Y.; Delorme, A.; Gold, R. D.
Abstract: Observations of recent earthquake surface ruptures show that ground deformations include a localized component occurring on faults, and an off‐fault component affecting the surrounding medium. This second component is also referred to as off‐fault deformation (OFD). The localized component generally occurs on complex networks of faults that connect at depth onto a unique fault plane, whereas OFD consists of distributed fracturing and diffuse deformation of the bulk volume, and occurs over scales of hundreds of meters to kilometers around the faults. High‐resolution optical image correlation presents a unique potential to characterize the complexity of the surface displacements, including on‐fault displacements and OFDs. In this study, we used sub‐pixel correlation of 0.5‐m resolution optical images to measure the surface displacement field with a <20 cm accuracy for a 30‐km long section of the 2013 M w 7.7 Baluchistan, Pakistan, rupture. Our results document significant variability in the fault displacements, associated with large proportions of OFD in regions of fault geometrical complexity. Conversely, in regions where the fault geometry is simple, surface deformation is entirely accommodated by the primary faults with 0% OFD. When combining the localized deformation on faults with the OFD, we show that the total surface displacement budget is constant along the strike of the rupture, despite strong variations observed in the rupture geometry. Based on this analysis, we propose an idealized scenario of earthquake surface deformation as a function of the rupture geometrical variations. Plain Language Summary: The 2013 M w 7.7 Baluchistan earthquake produced a 220 km‐long fault rupture in the Makran region in Pakistan. Because it is a military conflict zone, no field observations could be made, and the earthquake was studied exclusively using seismic, GNSS, and satellite data. In this work, we correlate high‐resolution (0.5 m) pre‐ and post‐earthquake optical images to measure the 3D ground displacement field for a 30 km‐long section of the rupture. This allows us to perform a detailed budget of surface deformation, including displacements on the different faults, and low‐amplitude deformation (10 −2 to 10 −3 ) of the medium up to 1 km from the faults. We show that the distant deformation occurs around the two major fault geometrical complexities present in our study area. In fact, we measure lower fault displacements across these complexities than across regions of simpler fault geometry. However, when considering both the displacements occurring on the faults and the distant deformation of the medium, we obtain a total surface displacement that is constant along the entire study area. This shows that, in this case, fault geometrical complexity did not prevent the surface deformation from occurring, but favored the distribution of the deformation over wider regions around the faults. Key Points: East‐west, north‐south, and vertical surface displacement maps are calculated at 0.5 m ground resolution We show the role of off‐fault deformation in accommodating surface displacements across km‐scale fault geometrical complexities Total coseismic surface displacement is constant along the study area, despite strong variations in the rupture geometry